1,3-Butanediol Administration Increases β-Hydroxybutyrate Plasma Levels and Affects Redox Homeostasis, Endoplasmic Reticulum Stress, and Adipokine Production in Rat Gonadal Adipose Tissue - Giuliana Panico; Gianluca Fasciolo; Vincenzo Migliaccio; Rita De Matteis; Lillà Lionetti; Gaetana Napolitano; Claudio Agnisola; Paola Venditti; Assunta Lombardi (MDPI AG, 2023)
Ketone bodies (KBs) are an alternative energy source under starvation and play multiple roles as signaling molecules regulating energy and metabolic homeostasis. The mechanism by which KBs influence visceral white adipose tissue physiology is only partially known, and our study aimed to shed light on the effects they exert on such tissue. To this aim, we administered 1,3-butanediol (BD) to rats since it rapidly enhances β-hydroxybutyrate serum levels, and we evaluated the effect it induces within 3 h or after 14 days of treatment. After 14 days of treatment, rats showed a decrease in body weight gain, energy intake, gonadal-WAT (gWAT) weight, and adipocyte size compared to the control. BD exerted a pronounced antioxidant effect and directed redox homeostasis toward reductive stress, already evident within 3 h after its administration. BD lowered tissue ROS levels and oxidative damage to lipids and proteins and enhanced tissue soluble and enzymatic antioxidant capacity as well as nuclear erythroid factor-2 protein levels. BD also reduced specific mitochondrial maximal oxidative capacity and induced endoplasmic reticulum stress as well as interrelated processes, leading to changes in the level of adipokines/cytokines involved in inflammation, macrophage infiltration into gWAT, adipocyte differentiation, and lipolysis.